2016
DOI: 10.1094/phyto-07-15-0159-r
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated with Severity of Bacterial Canker and Wilt Caused by Clavibacter michiganensis subsp. michiganensis in Tomato Greenhouses

Abstract: Clavibacter michiganensis subsp. michiganensis, the causal agent of bacterial canker and wilt of tomato, is considered to be one of the most important bacterial pathogens worldwide. In the year 2000 there was an increase in the number of infected greenhouses and in the severity of the disease in Israel. As part of the effort to cope with the disease, a comprehensive survey was conducted. Scouts recorded disease severity monthly in 681 production units. At the end of the season the scouts met with the growers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…The first peak was at 2.5 km with z-score of 14.41 (p = 0.000), and second and third peaks were found at 3.75 and 7 km with z-score of 17.52 (p = 0.000) and 23.91 (p = 0.000) respectively. The first peak tends to best describe the spatial variation of the analysis and is recommended for use when multiple peaks are present ( 27 , 31 ). In this study, a smaller spatial scale using the distance value at the first peak was assumed suitable to reflect more localized variations of traffic crash hot spots.…”
Section: Methodsmentioning
confidence: 99%
“…The first peak was at 2.5 km with z-score of 14.41 (p = 0.000), and second and third peaks were found at 3.75 and 7 km with z-score of 17.52 (p = 0.000) and 23.91 (p = 0.000) respectively. The first peak tends to best describe the spatial variation of the analysis and is recommended for use when multiple peaks are present ( 27 , 31 ). In this study, a smaller spatial scale using the distance value at the first peak was assumed suitable to reflect more localized variations of traffic crash hot spots.…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial canker of tomato, caused by Clavibacter michiganensis ssp. michiganensis ( Cmm ), is considered to be a serious threat to the processing and fresh market tomato industries, having caused catastrophic epidemics in most tomato‐growing areas of the world (Blank et al ., ; Kleitman et al ., ; Smith, ; Volcani, ).…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the fact that the spread has increased among neighboring state as more states recorded a similar range of COVID-19 cases. Blank et al (2016) used a similar approach, observed spatial clustering of bacterial canker severity, and showed that disease severity had significant spatial autocorrelation with dominant pattern recognized as clustered. A drop in mean transmission distance throughout foot-and-mouth outbreaks was similarly reported by Salje et al (2016).…”
Section: Resultsmentioning
confidence: 98%